Rebranding the Republic: Rome and the 1960 Olympic Games. Issue 1 (2nd January 2017) - Martin, Simon
Abstract: The 1960 Rome Olympic Games were held at a pivotal moment in the history of modern Italy and its capital. At the height of the 'economic miracle', tourists, international movie stars and entertainers, in addition to a record number of international athletes, flocked to the city to participate in the Games and the dolce vita . As a great 'national' project within a global and European context, Rome 1960 offered the organizers and ruling Christian Democratic Party (DC) the opportunity to rebrand Italy and show how far the country had come since the fall of Fascism and the end of the Second World War. While Rome 1960 was a marketing success – Italy's international reputation was significantly enhanced – close examination of the preparations for the tournament, as well as the Games itself, reveals significant continuities, deep and unresolved political and social tensions, evidence of corruption, and a failure to come to terms with Italy's recent past and the memory of Fascism. Questioning the extent to which the 1960 Olympics was a turning point in Italian sport and society, it exposes the Italy that existed beneath the sheen: one of stagnation, minimal change, political division and corruption.